Contribution of different body segments in Sit and Reach Test - Perin, Andrea (2015)
This research aims to determine the contributions of the hip joint, lumbar and thoracic spine in the execution of Sit and Reach (SR) in young Brazilians. Subjects were 195 boys from 18 to 19 years., Sit and Reach  was evaluated with angular kinematic analysis through of Photogrammetry to identify the contribution of body segments in trunk flexion.  A protocol was developed for evaluating reference angles that were transformed into percentage contribution of the segments. Based on the results, it was possible to create a table of classification of angles and percentages, which allowed the identification of compensation movement. It was possible to conclude that the contributions of the thoracic spine, lumbar spine and hip in performing the SR are 46.01±7.32%, 12.68±5.12% and 41.31±7.19% respectively. It is recommended that evaluations of flexion of the hip joint, thoracic and lumbar spine are performed separately by photogrammetry.